Performance Analysis of Eccentrically Braced Frames (EBF) using Metallic Yielding Damper (MYD) with Hysteretic Steel Damper (HSD) Type - Budi Suswanto; Fikri Ghifari; Triwulan Triwulan; Hidajat Sugihardjo; Pramesta Armanisag Pangestuti (Institute of Research and Community Outreach - Petra Christian University, 2025)
Eccentrically Braced Frames (EBFs) are earthquake-resistant steel structures with excellent shear capacity and ductility. During earthquakes, the EBF link yields first, protecting other structural elements. Traditionally, the link is integrated with the main beam and separated by bracing. However, if the link is damaged, replacing the entire beam becomes necessary. To address this, a vertical link design allows for link replacement without altering the beam section. This study evaluates two vertical link options: a Wide Flange (WF) link section and a Hysteretic Steel Damper (HSD) type Metallic Yielding Damper. Results suggest the WF link is preferable due to superior shear capacity and energy dissipation compared to the HSD link. The findings recommend the WF link for vertical link EBFs to optimize earthquake performance.